The concept of dimension in human resource management from Islamic management perspective - Ahmad Razimi, Mohd Shahril; Mohd Noor, Mohd Murshidi; Mohd Daud, Norzaidi (IDOSI Publications, 2014)
This paper is attempts to discuss the concept of dimension in human resource management (HRM) from Islamic management perspective.Based on library research, a few HRM dimensions are proposed, such as recruitment and selection, compensation, knowledge management, leadership and employee relations. In short, this paper is perhaps the first that discuss in detail on HRM from the Islamic management perspective.Hence, the findings of this study could assist policy makers on how to discover and understand new dimensions of human resource management from Islamic management perspective.